Investigating the Factors Affecting the Internal Development of Arid Cities (Case Study: Ardakan City) - Mohamadreza Hatafi Ardakani; Mohamadhosein saraei; mohamadmahdi karimnejad; seyed Ali Al_modaresi; Saeideh Moayedfar (تحقیقات کاربردی علوم جغرافیایی)
The rapid growth and horizontal expansion of cities in Iran may be more intense than in many developed and developing countries, as this process deprives most of Iran's historic cities of a monolithic urban structure and presents them with specific problems for balanced and balanced development. In addition, many old, dilapidated old land, land uses and textures within cities are in the midst of this accelerated, accelerated development, left out of urban development and proper urban development, and are now considered problematic urban contexts. The purpose of this study was to identify the factors affecting the inner development of the cities of arid regions. The present study is an applied one and a descriptive-analytic one. In this study, library and field method were used for data collection. In this study, Delphi technique as well as structural equation modeling in PLS software environment was used to achieve the research objectives. The statistical population of the study consisted of urban planning experts with a sample size of 30 individuals. The findings of this study showed that managerial, environmental, physical, spatial, economic, social and cultural factors play an important role in the development of Ardakan.